CHARACTERIZATION OF CELLULOSE FIBER ISOLATION FROM KAPOK RANDU (Ceiba pentandra) ON NaOH CONCENTRATION AND DELIGNIFICATION PROCESS TIME - Robbani, Syifa; Ichsan, Onne Akbar Nur; Sa'adah, Laila Mu'arifatus; Nanda, Ririn Fatma; Arwani, Muhammad (Agric, 2024)
Kapok range is a natural fiber that has considerable potential in the form of cellulose and can be enhanced by its physical and mechanical value cellulose. This study aims to analyze the character of cellulose produced from kapok and isolation. The cellulose isolation method used a factorial complete randomized design, namely the first factor of NaOH concentration (4%, 6%, and 8%) and the second factor of extraction time (40, 50, and 60 minutes). The cellulose isolation process showed that the method did not significantly affect the yield of randu kapok cellulose. The highest yield and degree of whiteness resulted from the treatment of 4% NaOH concentration and 40 minutes of extraction time with a yield of 6.54 ± 0.82%. The following result showed that the treatment had a significant effect on the results of the degree of whiteness. The highest degree of whiteness resulted from the treatment of 8% NaOH concentration and 60 minute extraction time of 30 ± 0.7. The cellulose isolation results of kapok resulted in cellulose content of 90.15 ± 0.81%, hemicellulose content of 3.6 ± 0.52%, and lignin content of 0.91 ± 0.03%. The analyzed properties provide a strong basis for considering the potential use of such cellulose nanofibers in various industrial applications, such as the manufacture of sustainable composite materials or other valueadded products.